Pengembangan Prestasi dan Pembinaan Kickboxing melalui Program PkM Kolaboratif di Kabupaten Ngawi Provinsi Jawa Timur - Fantas Setyadi; Yusuf Panji Antariksa; Bintang Oktaviandi Pratama; Diki Saputra (Universitas Teuku Umar, 2026)
Kickboxing performance training in Ngawi Regency still faces obstacles such as conventional, non-scientific training, limited World Association of Kickboxing Organizations (WAKO) standard coaching licenses, and weak organizational governance. This Collaborative PKM program aims to lay the foundation for long-term coaching through sports science interventions, coaching clinics, and governance assistance. The implementation method is carried out through three stages: preparation (coordination and module development), implementation (pre-test, periodization and injury management workshops, and practical clinics), and evaluation (post-test and formalization of partnerships). The evaluation results showed a significant increase in the cognitive capacity of coaches with an average increase in total understanding reaching 66.2%. The highest increase was achieved in the material on Sports Injury Prevention and Treatment (PPC) at 84.3%, which successfully reconstructed the conventional paradigm towards a scientific POLICE protocol. In addition, understanding of the Periodization & LTAD aspects increased by 61.9% and WAKO Technical Regulations increased by 55.1%. As a sustainability plan, this program produced a sports science-based Physical Training and Basic Techniques Guide Module and the signing of an Implementation Agreement (IA) with the Ngawi KBI Regency Government. In conclusion, this Collaborative PKM program effectively increased the instructional capacity of trainers and created a blueprint for standardizing training curricula to boost Ngawi Regency's Kickboxing achievements at the regional and national levels.